Afterglow of creation from the fireball to the discovery of cosmic ripples - Chown, Marcus 1959- (Univ. Science Books, 1996)
This is the story of the cosmic background radiation, the "afterglow" of the Big Bang in which the Universe was born. Fifteen billion years after the event, the afterglow still permeates all of space, making it the oldest relic in creation and providing an imprint of the Universe as it was in its infancy. But the most astonishing thing about the afterglow of creation is that it wasn't discovered until 1965, and then only by accident - despite the fact that it had been predicted in 1948 and the technology to detect it existed during World War II. Chown brilliantly weaves a tale of the search for the origins of the Universe. Beginning in the 1920s and culminating with the flight of the COBE satellite and what it found, this book uncovers the secrets of the Universe.